Integration of acoustic, optical, and electrical methods in picoliter droplet microfluidics for rare particles enrichment - Huasheng Zhuo; Chunhua He; Canfeng Yang; Xian Jiang; Fan Li; Xiangliang Yang; Hai Yang; Tuying Yong; Zhiyong Liu; Yan Ma; Lei Nie; Guanglan Liao; et al. (Communications Engineering)
Abstract Rare particle enrichment plays a pivotal role in advancing numerous scientific research areas and industrial processes. Traditional enrichment methods encounter obstacles such as low efficiency, high cost, and complexity. Acoustic focusing, optical fiber detection, and electrical manipulation have shown potential in microfluidics for particle manipulation and analysis. This study pioneers the integration of the acoustic, optical, and electrical units to overcome the traditional limitations. The cooperative dynamics of acoustic and flow focusing are explored. The optical fibers with an enhanced detection algorithm greatly boost optical detection sensitivity. Furthermore, the droplet charging to enhance the tip charging phenomenon is complemented and validated. The detection and sorting accuracy of enriching large-size H22 cells reached 99.8% and 99.3%, respectively, with the target cell concentration increased by nearly 86-fold. Our work significantly enhances detection sensitivity and particle manipulation accuracy, ultimately offering a robust and reliable solution for generating droplets to enrich rare particles.